Glutathione-related genetic polymorphisms are associated with mercury retention and nephrotoxicity in gold-mining settings of a Colombian population - Medina Pérez, Olga Marcela; Flórez-Vargas, Oscar; Rincón Cruz, Giovanna; Rondón González, Fernando; Rocha Muñoz, Linda; Sánchez Rodríguez, Luz Helena (Scientific reports, 2021)
Mercury (Hg) vapor can produce kidney injury, where the proximal tubule region of the nephron is the main target of the Hg-induced oxidative stress. Hg is eliminated from the body as a glutathione conjugate. Thus, single nucleotide polymorphisms (SNPs) in glutathione-related genes might modulate the negative impact of this metal on the kidneys. Glutathione-related SNPs were tested for association with levels of Hg and renal function biomarkers between occupationally exposed (n = 160) and non-exposed subjects (n = 121). SNPs were genotyped by TaqMan assays in genomic DNA samples. Total mercury concentration was measured in blood, urine and hair samples. Regression analyses were performed to estimate the effects of SNPs on quantitative traits. Alleles GCLM rs41303970-T and GSTP1 rs4147581-C were significantly overrepresented in the exposed compared with the non-exposed group (P < 0.01). We found significant associations for GCLM rs41303970-T with higher urinary clearance rate of Hg (β = 0.062, P = 0.047), whereas GCLC rs1555903-C was associated with lower levels of estimated glomerular filtration rate in the non-exposed group (eGFR, β = − 3.22, P = 0.008) and beta-2-microglobulin in the exposed group (β-2MCG, β = − 19.32, P = 0.02). A SNP-SNP interaction analysis showed significant epistasis between GSTA1 rs3957356-C and GSS rs3761144-G with higher urinary levels of Hg in the exposed (β = 0.13, P = 0.04) but not in the non-exposed group. Our results suggest that SNPs in glutathione-related genes could modulate the pathogenesis of Hg nephrotoxicity in our study population by modulating glutathione concentrations in individuals occupationally exposed to this heavy metal.